The Political Economy of Purity: Chhaupadi, Feudal Legacies and Intersectional Social Justice in Nepal - Shah, Debi Kumari (HPE Forum, 2026)
The embedded tradition of the chhaupadi in Nepal drives the women on their menstruation through narrow life-threatening sheds. That arrangement reveals the ugly separation of fundamental rights of respect. Instead of depending on the mainstream feminist perspectives that focus on tradition, this work relies on Critical Political Economy of Health coupled with Socialist and Materialist Feminism to discuss the problem. The core point? Chhaupadi is not some gull attitude of backward tradition but it is framed with historic traditions of power inequity. This habit is maintained by two types of control combined together. One is delicate which is based in ancient and conventional wisdom of Hindu concept of cleanliness and supported closely by social status and birth. The other type is harder it is about money and politics, nurtured by the ineffectiveness of government acts, fairness of resource distribution, or exclusion founded on location. Statistics indicate that the extent to which Chhaupadi is lethal thrives on the confusion between wealth and caste status and place of residence. Maintaining this tradition is therefore a pointer of gross injustice and implicitly it indicates the involvement of the state. The elimination of Chhaupadi is never stuck away with a either oldstyle awareness campaign or quick fix commodities. Rather, it demands reforms that are based on fairness that hold leaders accountable, redistribute resources equally, and turn around the deep power imbalances in health systems that allow harm to go unpunished.